Foreign Language Faculty Research-Related Beliefs, Perceptions, and Research Motivation at Three Mexican Universities (2018)
This paper examines the research self-efficacy beliefs, research motivation, and perceptions of research importance and research obstacles of 100 professors and lecturers of foreign languages at three Mexican universities. Survey results show that faculty hold moderate to high research self-efficacy beliefs, are highly motivated to conduct research, think research in the area is very important, and perceive that lack of time is the main obstacle to conducting research. The lack of fit between most participants’ relatively high self-efficacy and limited research engagement suggests the possibility that faculty overestimate their research abilities. The implications of these findings are also discussed.